1988
DOI: 10.1080/00107518808222607
|View full text |Cite
|
Sign up to set email alerts
|

Recent developments in the physics of liquid crystals

Abstract: Some of the more recent advances in the field of liquid crystals are summarized, with emphasis on the experimental developments rather than their theoretical implications. A major part of the discussion is devoted to newly discovered phases and phase transitions, particularly those that are of special interest to condensed matter physicists. Observations are also described of two new phenomena, which, although predicted by the continuum theory, have eluded experimentalists for many years: (a) the appearance of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0

Year Published

1989
1989
2002
2002

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 119 publications
0
8
0
Order By: Relevance
“…In other words, the time average of the molecular positions form a one-dimensional density wave. Many different smectic modifications have been identified, namely, smectics A to K [1]. We can roughly classify these rich variety of smectic phases into tilted and untilted phases depending on whether the molecules on average are tilted or untilted against the layers.…”
mentioning
confidence: 99%
“…In other words, the time average of the molecular positions form a one-dimensional density wave. Many different smectic modifications have been identified, namely, smectics A to K [1]. We can roughly classify these rich variety of smectic phases into tilted and untilted phases depending on whether the molecules on average are tilted or untilted against the layers.…”
mentioning
confidence: 99%
“…Now, though, these very defects are being harnessed in the zenithal bistable display, which unlike traditional LCD displays, does not require sustained power to retain an image (Mottram and Sluckin 2000). Also, the presence of defects is necessary for the stabilization of some of the blue phases observed in cholesteric liquid crystals, wherein the regular three-dimensional lattice is actually composed of disclination lines (Chandrasekhar 1988;Kléman 1989). In addition, recent research has shown the important effect of disclinations on the reduction of the nematic-isotropic phase transition temperature in nematic liquid-crystals (Mottram and Sluckin 2000;Mottram and Hogan 1997).…”
Section: Introductionmentioning
confidence: 99%
“…A system consisting of anísotropíc molecules exhibits two kinds of long-range ordering: long-range ordering of the centres of mass of the molecules or positional ordering and long-range ordering of the orientations of the molecules or orientational ordering [1][2][3][4][5][6]. When this system "melts" into an isotropic liquid usually both kinds of ordering disappear at the same temperature.…”
Section: Introductionmentioning
confidence: 99%
“…2.2.1, we can establish some relations among the interaction constants and relate the "shape" of ordering to the parameters of the model, particularly to the microscopic shape of the ellipsoidal molecules. Besides the orientational ordering in nematics studied and before [3], the new achievements in this work are the possibility of obtaining a biaxial ordered liquid state in the case of the system of ellipsoids, which are not axially symmetric; the orientational glassy structure and a simple explanation of orientational ordering in solid hydrogen (ortho-Η 2 or para-D 2 ) and, also, the presence of an ordered (uniaxial) phase of a disc-like (oblate) type when the temperature and the concentration are decreased in the system of nonmigrating ellipsoids. where Qxx = Q 11 Q 1 , Qyy = Q22 = Q2 and Qzz = Q33 = Q.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation